C-Met targeting in advanced gastric cancer: An open challenge. Issue 1 (28th August 2015) - Marano, Luigi; Chiari, Rita; Fabozzi, Alessio; De Vita, Ferdinando; Boccardi, Virginia; Roviello, Giandomenico; Petrioli, Roberto; Marrelli, Daniele; Roviello, Franco; Patriti, Alberto
Highlights Different compounds targeting c-Met have been developed and tested in gastric cancer. Discouraging outcomes of anti-c-Met monoclonal antibodies has been recently underlined. No clear anti-tumor activity was identified in small molecule c-Met inhibitors except for high c-Met-positive tumors. Several biomarkers are being explored in order to clarify the question of potential treatment benefits in selected patients.